HUBUNGAN LAYANAN BIMBINGAN KELOMPOK DENGAN MOTIVASI BELAJAR SISWA KELAS XI SMA ISLAM PB. SOEDIRMAN 2 BEKASI - Salohot Batubara; Puspita Permata Sari (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2018)
This research was conducted at SMA Islam PB. Sudirman 2 Bekasi. The techniqueused in data collection that uses literature, observations, and questionnaires. In this study,the author uses descriptive analysis method with a correlation test and t test. Thepopulation in this study were 80 students, which used a sample of 30 students with clusterrandom sampling technique. Then test the validity of the results of 60 items by productmoment formula using SPSS version 17 and the calculation of the reliability of theobtained results 0736, then declared reliable with a strong degree of reliability.Based on the results obtained from test data correlation, known correlation value is highat 0.495 with a significance level of relationship through t test calculation that t> t table(3,468> 1,701). then with these results, means the final hypothesis is the null hypothesis(HO) is rejected and the alternative hypothesis (HI) is received. It was concluded thatthere is a fairly high among group counseling services with the motivation to learn atSMA Islam PB. Sudirman 2 Bekasi